1996
DOI: 10.1143/jjap.35.2445
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Poly-Si Potential on Profile Distortion Caused by Charge Accumulation

Abstract: The appearance of local side etch in polysilicon etching was investigated using a pattern of lines and spaces (L&S) with spaces of various widths. The local side etch is found to appear at lines connected to the silicon substrate even when there is no exposed area of the silicon substrate. It is also found that the degree of local side etch decreases as the area of exposed silicon substrate increases. From these results, it is considered that the cause of the local side etch is the electron supplied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
3
9
0
Order By: Relevance
“…Thus, a correlation between this potential difference and the notch depth is expected to exist. We note that the potential distribution in the trench region remains unchanged for open area widths greater than 5 m. Thus, the notch profile for Wϭ10 m is identical to the one obtained for Wϭ5 m. Our findings discredit the conjecture that electron accumulation at the outermost line is determined solely by the solid angle available to electrons to reach the poly-Si sidewall, 16 which predicts that the notch depth should increase continuously with the open space width.…”
Section: F Notching Dependence On the Open Area Widthsupporting
confidence: 67%
See 1 more Smart Citation
“…Thus, a correlation between this potential difference and the notch depth is expected to exist. We note that the potential distribution in the trench region remains unchanged for open area widths greater than 5 m. Thus, the notch profile for Wϭ10 m is identical to the one obtained for Wϭ5 m. Our findings discredit the conjecture that electron accumulation at the outermost line is determined solely by the solid angle available to electrons to reach the poly-Si sidewall, 16 which predicts that the notch depth should increase continuously with the open space width.…”
Section: F Notching Dependence On the Open Area Widthsupporting
confidence: 67%
“…1,16 The notch depth depends weakly on the total poly-Si perimeter bordering the open area; a three order-of-magnitude change in the perimeter doubles the notch depth under identical etching conditions. 1 Our 2D simulation cannot be used to predict quantitatively the effect of the perimeter, unless the lines are connected through the substrate.…”
Section: G Notching In Electrically Connected Poly-si Linesmentioning
confidence: 99%
“…In the same figure, the notch depth is shown to increase linearly with the substrate area exposed to the plasma, capturing the experimental results of Ogino et a. 7 (see their Fig. 1 0).d The linear relationship is expected to break down upon further increase of R, as the substrate potential decreases more slowly beyond R = 0.5.…”
supporting
confidence: 83%
“…Moreover, this high-density plasma can cause profile distortion such as local side etch during polysilicon etching on a dielectric film such as gate silicon dioxide. Many studies regarding this profile distortion have been reported, and the charge-up of patterns, called the electron shading effect, is suggested as the model of the local side etch [9,10]. Depending on the plasma state and parameters, many problems arise.…”
Section: Introductionmentioning
confidence: 99%